What Influences Parents and Practitioners' Decisions to Share Personal Information within an Early Help (Social Care) Context? Implications for Practice in Sharing Digital Data across Sectors. (20th August 2021) - Smart, Deborah; Jackson, Katherine; Alderson, Hayley; Foley, Thomas; Foreman, Stephen; Kaner, Ben; Kaner, Eileen; Lancaster, Helen; Lingam, Raghu; Rankin, Judith; Rowlands, Gill; Spencer, Liam; et al.
Abstract: Meeting the multiple and often complex needs of families (children, young people and adults) within 'Early Help' support is dependent upon practitioners from different sectors sharing relevant and timely information, after gaining a family's voluntary consent to share information. This article reports on qualitative one-to-one interviews with adults in families ( n  = 32), one mother/father dyad interview ( n  = 2) and focus groups with practitioners ( n  = 47) in five local authority areas in North East England receiving or providing Early Help support. We explored experiences of providing consent to share personal information and consider the usefulness of a digital health data system when providing Early Help support to families. Communication Privacy Management theory was used as a framework to analyse the data. Key themes in participants' accounts include the degree of need for help and support; the importance of trusting relationships; stronger and structured joint working practices; and understanding how information is shared. This work provides insights into current information sharing practices for some of the most vulnerable families and the wider social contexts. It has implications for the usefulness of a digital data system that shares GP health data with Early Help services and suggests the role this could have in the parent–practitioner relationship. Abstract : Early Help support can be provided to children and their families as soon as a problem emerges, to help them overcome the challenges they face. This support is voluntary and for practitioners to share information about a family's circumstances with another organisation, parents are required to give their permission for this to happen. There are several factors that can influence if and how information sharing happens. These factors should be considered when designing new ways of sharing information such as digital data sharing systems.